Crossing Surfaces in Search of the Holy: Landscape and Liminality in Contemporary Christian Pilgrimage. (May 2013) - Maddrell, Avril; della Dora, Veronica
This paper examines the role of surfaces in pilgrimage practices and experiences in two denominational and cultural contexts and landscape settings for Christian pilgrimage: a week of Ecumenical pilgrimage walks in the Isle of Man and Orthodox pilgrimage to the monasteries of Meteora in Greece. Surfaces are examined as dynamic textured platforms for journeying and stages for the performance of ritual; as part of visual aesthetic and multisensory embodied experiences; as hermeneutical texts; as perceived liminal thresholds through which the divine might be experienced; and as tangible material fragments encapsulating and facilitating the 'taking home' of the pilgrim experience. Surfaces are found to be significant for pilgrims in a variety of shared ways, but also ways which are inflected by different theological and cultural contexts. Through its analysis of faith adherents and practices, this study offers (i) a spiritually informed perspective on both perceptions and experiences of surfaces, and (ii) understanding of faith-inflected mobilities and 'more-than-representational' meanings and practices.